'Isaac went out to the field' : studies in archaeology and ancient cultures in honor of Isaac Gilead - Gilead, Isaac,; Goldfus, Haim, 1951-; Gruber, Mayer I.; Yonah, Shamir,; Fabian, Peter, (Archaeopress Publishing Ltd, 2019)
This work presents 28 articles honouring Professor Isaac Gilead on his 71st birthday. Papers on prehistoric and proto-historic archaeology reflect the focus of the honoree's teaching and research, while other subjects including Biblical and Near Eastern studies explore Gilead's other areas of interest.